Occurrence and Human Exposure Assessment of Parabens in Water Sources in Osun State, Nigeria - Alfred, Moses Oladele (Science of the Total Environment, Elsevier, 2022)
Parabens are chemicals extensively used in pharmaceuticals, cosmetics, personal hygiene and food products as preservatives. They are classified as emerging contaminants with endocrine-disrupting capability. In this study, the concentrations of Methylparaben (MeP), Ethylparaben (EtP), Propylparaben (PrP) and Butylparaben (BuP) were obtained from groundwater, surface-water and packaged water samples collected from urban and rural areas of Osun State, Nigeria using HPLC-UV equipment. Data obtained were subjected to descriptive (Mean ± SD), inferential (KruskalWallis test) and multivariate analyses. MeP had the highest average concentration of 163 and 68 μg L−1 in surface water and groundwater respectively while concentrations of MeP, EtP, PrP and BuP were higher than previously reported in other countries. Methylparaben had the highest detection frequencies (88.0 and 50.0%) followed by BuP (69.0 and 50.0%) in surface water and groundwater respectively. No significant difference was observed for concentrations of parabens in groundwater samples in urban and rural sampling sites, suggesting that people living around these sites are equally exposed to any health implications from the use of paraben-polluted potable water. Principal Component Analysis (PCA) data suggest that the pairs MeP & EtP, PrP & BuP (in surface water samples) and MeP, EtP, & PrP (in groundwater samples) are from similar pollution sources. Ecological risk assessment using Algae, Fish, and Daphnia suggests Daphnia as the most sensitive organism while BuP and PrP show the highest health risk. Human exposure assessment showed that higher overall median estimated daily intake (EDI) values for groundwater were observed in infants (1.71 μg kg−1 bw day−1, ∑PBs) compared to toddlers (1.03 μg kg−1 bw day−1, ∑PBs), children (0.64 μg kg−1 bw day−1, ∑PBs), teenagers (0.51 μg kg−1 bw day−1, ∑PBs) and adults (0.62 μg kg−1 bw day−1, ∑PBs). Although these values are below limits set in a few countries, potential bioaccumulation could lead to severe health consequences.